Concordance between introductory university mathematics courses and the program of pre-university studies: A view from the perspectives of content and academic performance - Castillo-Sánchez, Mario (2018)
This article reports data about academic achievement in introductory university level mathematics courses taught by the Department of Mathematics at the Universidad Nacional de Costa Rica and the concordance between the contents of these courses and those of pre-university (secondary education) programs. Information was collected by analyzing grades from introductory university mathematics courses for all programs of study in the period 2011-2016, the courses offered, and the program of studies in mathematics in secondary education. This was done to determine academic performance and to make comparisons between introductory mathematics courses at university level and the program of mathematics studies in secondary education, to stimulate revision and updating of the courses and generate recommendations. The results show that there are high failure and dropout rates in most introductory university-level mathematics courses, and that there are differences between the content that students study in secondary education and the content of introductory mathematics courses offered by the Universidad Nacional; prior knowledge is therefore relevant for academic achievement in introductory university mathematics courses. In addition, the data collected on content and aspects of methodology and evaluation show important differences in the way mathematical contents are addressed at each level. This implies that analysis of the contents of these courses should be carried out and strategies should be created, to guarantee a minimum level of prior knowledge in students when beginning the study of these subjects at university level.